Fake news 'yan exploring generation Z Filipinos responses to online information - Palacio, Matthew Jolo B.; Solteo, Nicole Vianne C.; Sursoga, Lea P.; Tonolete, Angel Graciela S.
The rapid proliferation of online misinformation in the Philippines has become a pressing issue nationwide since Filipinos are overly exposed to social media. Moreover, the overconfidence of online users in their ability to critique and discern information found on social media platforms exacerbates the problem. Previous research has acknowledged that Generation Z Filipinos have a general undertaking of fake news, its intent or purpose, and the personality traits that tend to spread misinformation, little investigation went into the factors that influence their assessment of an information's legitimacy. This qualitative study explored the key identifiers that influence the evaluation of online information legitimacy among 18-19-year-old Generation Z Filipinos. The researchers utilized a photo-elicitation interview method to gather data, which was analyzed using Krippendorf's convenient content analysis approach. The findings revealed that "HAHA" engagements played significant role in influencing their perception of information legitimacy. Furthermore, the news format and presentation, disseminators, and sources, and overall content of the news influenced their perception of information legitimacy. Furthermore, the news format and presentation, disseminators, and sources, and overall content of the news influenced their perception of the new's credibility. The study also highlighted the importance of public and prior knowledge as a key identifier in spotting fake news. This shed light on the dynamics of information evaluation among Generation Z Filipinos. Comprehending the different factors that influence their assessment aids in the development of interventions to help mitigate the impact of online misinformation in the country.